PERILAKU DINDING KOMPOSIT ANYAMAN BAMBU-MORTAR TERHADAP BEBAN LATERAL - , VECTOR REIHARD REDOLF HUTUBESSY ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objective of this research was to investigate capacity of plaster-wall. A series of test was conducted on three kinds of plaster-wall, namely without bracing (DP-TB), with bamboo bracing (DP-BB), and steel wire mesh bracing (DP-BK). Method used was static load (monotonic) to determine relationships between lateral load and deflection of plaster wall. The monotonic test was applied until the load decreased to 20% of peak load. The results showed that wall DP-BK have higher peak load, energy dissipation and ductility than DP-BB. Elastic stiffness of wall DP-BB was 1.27 times higher than DP-BK. The ultimate load resulted from the experiment for DP-BB and DP-BK make 25.52 kN and 26.37 kN, respectively, or twice larger than the flexural failure analysis result based on Subedi (1991) method, which was 14.39 kN.